Александр Блок и русская литература Серебряного века - Pild, Lea (Acta Slavica Estonica, 2015)
Acta Slavica Estonica is an international series of publications on current issues of Russian and other Slavic languages, literatures and cultures. This issue of the subseries "Blokovskii sbornik" continues the series of studies started by Zara Mints in 1964. The majority of works from Section I of the book, "The Art of А. Blok in the Context of 19th-20th Century Literature," is devoted to the study of the poet's works, his perceptions of preceding writers' works, and his biographical and artistic contacts with contemporaries. The articles in Section II, "Silver Age Literature: Creative and Social Strategies," are mainly focused on artistic works and essays of modernist literati contemporary to Blok or to some extent resonating with his poetry and artistic worldview.